Simultaneous adsorptive removal of Pb2+, Cd2+, Cu2+, and Zn2+ using raw Norway Spruce biomass: a low-cost and eco-friendly solution for wastewater treatment - Al-Labadi, Ibrahim G.; Horváth, Márk; Alkilani, Ayah T.; Al-Ma'abreh, Alaa M.; Bashir, Mohammed J. K.; Keshta, Basem E.; Hanbali, Ghadir; Al Zoubi, Wail; Abukhadra, Mostafa R.; Alqhtani, Haifa A.; Eid, Mohamed Hamdy (Frontiers in Water, 2025)
This study evaluated the unmodified Norway Spruce Wood Residue (NSWR), an abundant lignocellulosic biomass, for the simultaneous removal of Pb2+, Cd2+, Zn2+, and Cu2+ from a quaternary aqueous system. A series of batch adsorption experiments were performed to assess the influence of key operational parameters (pH, contact time, adsorbent dose, temperature, particle size, initial concentration), with equilibrium data subsequently fitted to Langmuir and Freundlich isotherm models, and the NSWR characterized using FTIR and EDS analyses. The results demonstrated maximum Langmuir adsorption capacities following the order Pb2+ (10.3 mg/g) > Cu2+ (7.9 mg/g) > Cd2+ (6.3 mg/g) > Zn2+ (6.0 mg/g), corresponding to high removal efficiencies (up to 99% for Pb2+). Adsorption was rapid initially (~60% removal within 20 min) and favored slightly acidic conditions (pH 5–6) and moderately elevated temperatures (45°C). The Langmuir model provided an excellent fit to the data (R2 ≈ 0.99), indicating favorable monolayer chemisorption, likely driven by a combination of cation exchange supported by EDS and interactions with surface functional groups. Conclusively, unmodified NSWR shows significant promise as an effective, inexpensive, and eco-friendly biosorbent for treating water contaminated with multiple heavy metals, presenting a viable waste valorization strategy for sustainable water management.